The Hydric Environment: A Hub for Clinically Relevant Carbapenemase Encoding Genes - Florence Hammer-Dedet; Estelle Jumas-Bilak; Patricia Licznar-Fajardo (MDPI AG, 2020)
Carbapenems are β-lactams antimicrobials presenting a broad activity spectrum and are considered as last-resort antibiotic. Since the 2000s, carbapenemase producing Enterobacterales (CPE) have emerged and are been quickly globally spreading. The global dissemination of carbapenemase encoding genes (CEG) within clinical relevant bacteria is attributed in part to its location onto mobile genetic elements. During the last decade, carbapenemase producing bacteria have been isolated from non-human sources including the aquatic environment. Aquatic ecosystems are particularly impacted by anthropic activities, which conduce to a bidirectional exchange between aquatic environments and human beings and therefore the aquatic environment may constitute a hub for CPE and CEG. More recently, the isolation of autochtonous aquatic bacteria carrying acquired CEG have been reported and suggest that CEG exchange by horizontal gene transfer occurred between allochtonous and autochtonous bacteria. Hence, aquatic environment plays a central role in persistence, dissemination and emergence of CEG both within environmental ecosystem and human beings, and deserves to be studied with particular attention.